RETRACTED: Developing an Android Based Application as Balinese Shadow Puppet Educational Media - Gede Doni Agustina; I Gede Mahedra Darmawiguna; I Made Gede Sunarya (Faculty of Engineering, Universitas Negeri Yogyakarta, 2017)
RETRACTEDFollowing a rigorous, carefully concerns and considered review of the article published in Jurnal Pendidikan Teknologi dan Kejuruan entitled “Developing An Android Based Application as Balinese Shadow Puppet Educational Media” Vol 23, No 3, pp. 241-249, May 2017 DOI: http://dx.doi.org/10.21831/jptk.v23i3.13387This paper has been found to be in violation of the Jurnal Pendidikan Teknologi dan Kejuruan Publication principles and has been retracted.The article contained redundant material, the editor investigated and found that the paper published in Kumpulan Artikel Mahasiswa Pendidikan Teknik Informatika (KARMAPATI) ISSN: 2252-9063, Vol. 4, No. 4, 2015The document and its content has been removed from Jurnal Pendidikan Teknologi dan Kejuruan, and reasonable effort should be made to remove all references to this article.